The features of identification anthropogenic risks of chemical - technological objects on the design stage - Бойко, Тетяна Владиславівна; Назаренко, Маргарита Вячеславівна; Бендюг, Владислав Іванович (Eastern-European Journal of Enterprise Technologies, 2012)
The article presents a method of using indices for evaluating the technological risk of chemical – engineering objects at the design stage. Indexes of relative risk were calculated, category of hazard object were analyzed. The results for technological objects were represented